Framing PIGS: patterns of racism and neocolonialism in the Euro crisis - Van Vossole, Jonas (2016)
Van Vossole's article explores the racist framing of the peripheral member states of the European Union, the PIGS (Portugal, Ireland (and/or Italy), Greece and Spain). It demonstrates a strong connection between the processes of racialization and depoliticization, as well as the return of colonial dynamics in the Eurozone. Side-stepping political economy and history, the culturalization of politics perfectly complements the ‘post-political’ neoliberal hegemony. Political and media discourses reproduce it in both populist and corporate interests. The culturalization of politics reduces the differences between centre and periphery to certain ‘cultural characteristics and habits’, as reflected in stereotypes of laziness, non-productivity, corruption, wasteful spending and lying. These make it possible to blame the PIGS for the current crisis, legitimizing drastic austerity measures and a loss of sovereignty. The loss of sovereignty shows remarkable similarities with what Kwame Nkrumah defined as neocolonialism: the continuation of colonial power relations through processes of economic dependence, conditional aid and cultural hegemony. While this problematic only resurfaced during the recent Euro crisis, Van Vossole discusses how today's racist discourses and neocolonial politics have their roots in the past, particularly in anti-Irish and anti-Mediterranean racism and in the (semi-)colonial position of the PIGS in the British and Ottoman empires. Besides structural violence against the periphery, a major consequence of this racialization is that it jeopardizes any possibility of further democratic political integration on the basis of a common European identity.